Minimization of amplitude distortions for time-scale compression of speech signals - Zsymanski, Z. (Українські технології, 2006)
The algorithm of time-scale compression of speech signal, based on temporal reconstruction with the help of functions of temporal transforming, has been improved. Existing is signal amplitude distortions are reduced by the use of cross-correlation function and creating of intermediate composite segment.
Keywords: correlation; speech signal; time-scale compression